American Society of Clinical Oncology 2014: Updates in breast and gastrointestinal cancers - Dawood, Shaheenah (Medknow Publications & Media Pvt Ltd, 2014)
The last two decades have been very exciting in the realm of breast and GI oncology with a plethora of new information that has significantly impacted clinical practice. From the use of anti HER 2 agents in both the adjuvant and metastatic settings of breast cancer to the use of anti EGFR agents in the metastatic setting of colorectal cancer we have seen some significant advances in the treatment of these diseases. This year at ASCO 2014 data were presented that attempted to answer important clinical questions faced by a community oncologist in the clinic. This review focuses on important data presented for both breast and GI cancer.